DOES THE HEALTH CARE PROVIDER FULFILL THE NEEDS AND EXPECTATIONS OF WOMEN DURING INTRA-PARTUM AND IMMEDIATE POSTPARTUM PERIOD IN A SELECTED GOVT. HOSPITAL OF WEST BENGAL? - Khatun, Najnina; Mani, Smritikana (International Journal of Research -GRANTHAALAYAH, 2019)
A descriptive study was conducted to assess the needs and expectations and fulfilment of needs and expectations of intra-partum and immediate post partum women. The findings revealed that in the area of esteem need all women (100%) wanted respectful maternity care. Intra-partum women had different types of need i.e. physiological need (92%) personal and psychological need (90%) social needs (98.61%) and safety needs (95%). Among various types of intra partum need 61.54% physiological needs were totally fulfilled. Pain relieving needs of immediate postpartum women were totally fulfilled (100%). Statistically significant association were found between educational status and fulfilment of personal & psychological need (χ2 = 5.257) and gravida and fulfilment of informational needs (χ2 = 14.920) at df 1, p <0.05 level of significance. There was a moderate negative correlation (‘r’ = -0.548) found between gravid and intra partum and immediate postpartum needs. There was a significant mean difference (t= 5.399, at df 118) between fulfilment of needs of primigravida and multigravida women at 0.05 level of significance. The study has a implication in nursing service by assessing the needs & expectations of intra partum and immediate postpartum women, the total needs can be fulfilled by health care provider.